Creating a sustainable future? the working life of creative workers in Vienna. (1st January 2007) - Sybille Reidl; Helene Schiffbänker; Hubert Eichmann
Abstract : This article looks at the sustainability of work arrangements in Vienna's creative industries. Based on a survey of over 900 people who work in five sub-sectors (advertising, architecture, graphics/design/fashion, film/video/broadcasting and multimedia), it finds that there is significant pressure on those working in these industries. This results mainly from the fact that most are self-employed and consequently their guarantee of future work is insecure and they lack strategies to develop their own micro-businesses. The respondents have, however, developed coping strategies to deal with these pressures. In general, therefore, those with a high risk strategy in combination with high levels of work autonomy are more satisfied than creative workers who are employed and have a steady income but little decision-making freedom. Despite this, issues such as social security raise doubts about the future sustainability of their work. Further information about the project can be found on www.forba.at/kreativbranchen-wien .